(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2020)
The topic of employer branding and employee retention is attracting great attention of management researchers and practitioners. Employer branding is one way that increases value of organisations, which integrates two significant organisational fields of branding and human resources, and together they give an adjusted view on the most proficient way to pull in and retain required employees. In this regard, the present study aims at investigating the major dimensions of attractiveness in employer branding for human resource retention in Nepalese hospitality industry. The study employed a cross-sectional descriptive survey design including four out of seven dimensions of attractiveness in employer branding with a sample of 292 respondents from six five-star hotels of Nepal stationed in the capital Valley of Kathmandu. Using Kendall’s tau, correlation analysis and Jonckheere-Terpstra test- the descriptive statistics, the study discovered that economic value and interest value dimensions of attractiveness in employer branding for HR retention significantly vary according to hierarchy of the employees in Nepalese hospitality industry.